Academic discipline „Travel services market” in the digital age - Binytska, Olena (Journal of Education, Health and Sport, 2023)
The article discusses the possibility of using digital technologies in teaching the discipline ‘Market of tourist services. It is emphasised that digitalisation of education is a prerequisite for the training of competitive specialists in the tourism industry. The introduction of innovative technologies, such as artificial intelligence capabilities, immersive technologies, and large data sets, are changing approaches to teaching professional disciplines, providing students of the speciality ‘Tourism’ with opportunities for the development of professional skills. The article also analyses how to use online platforms, social media and content marketing when studying the course ‘market of tourist services’. Thus, the article emphasises the importance of digital transformation in education and tourism business, which contributes to better training of competitive professionals and meeting the needs of modern consumers in the tourism industry.